Multimodal Psychotherapeutic Inpatient Therapy of Depression Is Successful in Patients With High Cytokine Production - Peters, Eva M. J.; Neusetzer, Melanie; Akinci, Secil; Murat, Aysenur; Treuherz, Sabine; Rose, Matthias; Leweke, Frank; Leichsenring, Falk; Conrad, Melanie L.; Kruse, Johannes (Frontiers in Psychiatry, 2020)
Objective: In experimental settings, systemically elevated inflammation markers interfere with major depression treatment. In German healthcare, compulsory national health insurance covers treatment of a wide variety of depressive disorders if it follows evidence-based medicine guidelines combining recommended therapies. To date, little is known about the relevance of immune system cytokine production with regard to real-world clinical care for patients with moderate depression. Methods: 73 patients with moderate depression subjected to multimodal psychotherapeutic inpatient therapy (mPT) following a psychodynamic concept at a German university hospital were included. As a primary outcome, mPT success, evidenced by delta HADS `depression´, was analyzed according to tumor necrosis factor alpha (TNF) production by peripheral blood mononuclear cells (PBMC) after phytohemagglutinin (PHA) challenge at baseline. Secondary outcomes addressed the inflammatory response and mental health comparing high and low TNF-producers. Results: First, higher PBMC TNF production at baseline predicted a better mPT-outcome (R2 0.162, p=0.014). Second, patients with high TNF (hTNF) at baseline produced significantly more acute inflammatory cytokines (interleukin [IL]1, IL6), TH1/TH2 cytokines (interferon gamma [IFN], IL4) as well as eotaxin and IL2 compared to low TNF producers (lTNF) (Cohen´s ds between -0.532 and -1.013). Demographic data, diagnosis subtype-distribution, medication; systemic inflammation markers (C-reactive protein [CRP], high mobility group box 1 [HMGB1], leptin); anxiety and depression (HADS) did not differ. From baseline to mPT-discharge, HADS `depression´ decreased in both hTNF (11.31 to 5.47, p=0.001, d=1.184) and lTNF patients (11.50 to 7.92, p=0.001, d=-0.765), while PBMC cytokine production decreased significantly in hTNF (Cohen´s ds between -0.304 and -0.345) with a significant group by time interaction for TH1/TH2 ratio. At the end of therapy, comparison of TNF groups revealed significantly lower depression-scores in hTNF compared to lTNF patients (5.47 compared to 7.92, p=0.035, d=0.504). Conclusions: Our study demonstrates successful treatment of depression in a clinical care setting using multimodal psychotherapy based on a psychodynamic concept following guideline recomondations. The greatest improvement in patient depression was linked to highest production of TNF by PBMCs at baseline. Our study contributes to the definition of patient subpopulations with differing cytokine responses that are related to succesful treatment of depression.